2021
DOI: 10.12928/telkomnika.v19i1.16507
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dualband fan-shaped microstrip bandpass filter

Abstract: In this study, design and simulation of microtrip bandpass filter is presented using RT/Duroid 6010.2 lm substrate. This filter has fan-shaped topology with small dimensions of 12x12 mm 2 , designed for dual band frequencies at 3.41 and 6.14 GHz. The insertion loss and return loss of initial band at 3.41 GHz are-0.7 and-38.224 dB respectively and its bandwidth ranged from 3.3561 to 3.48 GHz. On the other hand, for 2 nd band at 6.14 GHz, the insertion loss and return loss have been-1.377 and-14 dB respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The simulated results showed an acceptable insertion loss value (𝑆 21 = −1 dB), however, a poor quality factor was achieved (𝑄=2.7) and the structure was deposited on the top face of a sizeable Rogers RO4003C substrate (>10×10 mm 2 ). In Abdulkareem et al [20], a fan-shaped microstrip bandpass filter was suggested. The simulated results are satisfying in term of reflection coefficient (𝑆 11 < −10 dB), but a slightly high insertion loss (𝑆 21 = −1.377 dB) was obtained and the structure was implemented on a large RT/Duroid 6010.2 dielectric substrate (12×12 mm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results showed an acceptable insertion loss value (𝑆 21 = −1 dB), however, a poor quality factor was achieved (𝑄=2.7) and the structure was deposited on the top face of a sizeable Rogers RO4003C substrate (>10×10 mm 2 ). In Abdulkareem et al [20], a fan-shaped microstrip bandpass filter was suggested. The simulated results are satisfying in term of reflection coefficient (𝑆 11 < −10 dB), but a slightly high insertion loss (𝑆 21 = −1.377 dB) was obtained and the structure was implemented on a large RT/Duroid 6010.2 dielectric substrate (12×12 mm 2 ).…”
Section: Introductionmentioning
confidence: 99%